Proceedings of 2010 IEEE International Symposium on Circuits and Systems 2010
DOI: 10.1109/iscas.2010.5537181
|View full text |Cite
|
Sign up to set email alerts
|

Complexity-effective dynamic range compression for digital hearing aids

Abstract: Dynamic range compression (DRC) is an essential function in digital hearing aids, which have stringent power consumption constraints. This work minimized the complexity of the DRC algorithm through adopting functional approximation for those involved nonlinear operations. The tradeoff between computation reduction and approximation error was explored for reducing hardware cost without introducing audible artifact. Moreover, finite wordlength analysis is conducted for the wordlength minimization and further com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Note that the result of SFB is not included in Table VII because the filter banks in the literature [7]- [14] have all considered AFB only. Moreover, SFB in a hearing aid SoC will likely be merged with dynamic range compressors for further optimization [6], [26]. The comparison results in Table VII validate the effectiveness of the proposed quasi-ANSI AFB.…”
Section: The Optimized Low-power Architecturementioning
confidence: 74%
“…Note that the result of SFB is not included in Table VII because the filter banks in the literature [7]- [14] have all considered AFB only. Moreover, SFB in a hearing aid SoC will likely be merged with dynamic range compressors for further optimization [6], [26]. The comparison results in Table VII validate the effectiveness of the proposed quasi-ANSI AFB.…”
Section: The Optimized Low-power Architecturementioning
confidence: 74%
“…The general requirement of less than 12 ms [2] prevents the loss of visual cues (un-synchronized) with respect to hearing. Stone and Moore [16], [17] indicated that a delay of 20-30 ms can be judged as objectionable for mild-to-moderate hearing loss. The popularity of open-canal (OC) fitting hearing aids, which leave the ear canal much more open than traditional close-fitting ear-molds, makes hearing aid delays even more concerning.…”
Section: Fig 3 Matching Capability Comparisons For Different Types mentioning
confidence: 99%
“…Different echo cancellation techniques could be implemented to cancel the echo or feedback [10], [11]. Hearing aids also use compression [4], [5], [6] which basically amplify the low level sounds more than the high level sounds. If the compression is not used the hearing aid will also amplify louder sound which will be painful.…”
Section: Types Of Hearing Aidsmentioning
confidence: 99%